2023
DOI: 10.3390/ma16020485
|View full text |Cite
|
Sign up to set email alerts
|

Study on Surface Integrity and Fatigue Properties of TC4 Titanium Alloy by Surface Ultrasonic Rolling

Abstract: In this paper, the influence of a surface ultrasonic rolling process on the surface integrity of TC4 titanium alloy and its influence on the fatigue properties were studied. By comparing and analyzing the surface roughness, microhardness, residual stress, microstructure, and fatigue fracture, the surface strengthening and modification mechanism of TC4 titanium alloy is discussed. The results show that the surface roughness of titanium alloy is observably decreased after the suitable surface ultrasonic rolling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Different USRP process parameters have different effects on the integrity of the sample surface. Hu et al [24] carried out USRP experiment on 60Si2CrVAT steel, and found that with the static pressure increased, the residual compressive stress firstly increased and then decreased, the hardness continued to increase. As rotate speed and feed rate increased, the hardness and residual compressive stress decreased, while the surface roughness increased.…”
Section: Introductionmentioning
confidence: 99%
“…Different USRP process parameters have different effects on the integrity of the sample surface. Hu et al [24] carried out USRP experiment on 60Si2CrVAT steel, and found that with the static pressure increased, the residual compressive stress firstly increased and then decreased, the hardness continued to increase. As rotate speed and feed rate increased, the hardness and residual compressive stress decreased, while the surface roughness increased.…”
Section: Introductionmentioning
confidence: 99%
“…The residual stress anisotropy has also been found in LSP, DR, and USRP [22, 23,24]. The residual stress anisotropy in LSP was further studied [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the relationship between surface roughness and the fatigue life of titanium alloys. Xiaotong Zhu et al [7] studied the effect of the surface ultrasonic rolling process on the surface roughness and fatigue properties of TC4 titanium alloy. The test parameters are a vibration frequency of 29 kHz, a current of 1 A, an amplitude of 0.007-0.008 mm, and a rolling ball diameter of 14 mm.…”
Section: Introductionmentioning
confidence: 99%